“Live right off the Land and Water”: Drag Seines, Capitalism, and Gitxaala Lifeway - Menzies, Charles (Anthropologica, 2025)
Drawing from community-based research in the author’s home First Nation, Gitxaała, this paper documents an articulation between a First Nations economy and the insertion of capitalism within their territories. Voices of Gitxaała hereditary leaders, matriarchs, and harvesters are prioritized and emphasized. The story that unfolds is of the cultural reliance and persistence of Gitxaała people in the face of economic transition.